Antiphospholipid Syndrome Handbook - Khamashta, M. A.; Bertolaccini, Maria L.; Ateka-Barrutia, Oier.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
Antiphospholipid Syndrome Handbook presents the major clinical features of antiphospholid syndrome, or Hughes$1 (BSyndrome, discussing diagnosis, treatment and management of the illness, in a handy short practical book. Bringing together the various areas of specialization that may encounter antiphospholipid syndrome, a section on clinical features focuses on various organs in turn, explaining how antiphospholipid syndrome may be manifested in the organ in question. Furthermore, guidance on antiphospholipid syndrome in pregnancy and pediatric antiphospholipid syndrome is included. This reader-friendly, quick pocket-reference is a useful guide to clinicians from general and internal medicine disciplines, and in particular to specialists in rheumatology, hematology, cardiovascular medicine, neurology, nephrology, dermatology, chest medicine and obstetrics. Munther A. Khamashta, MD, FRCP, PhD is Senior Lecturer, Guy$1 (Bs, King$1 (Bs & St Thomas$1 (BSchool of Medicine and Honorary Consultant Physician, , Rayne Institute, St Thomas$1 (BHospital, London, UK. He is a world leader in antiphospholipid syndrome, having worked in the field for over 20 years. Maria L. Bertolaccini, MD, PhD is Lecturer based at Lupus Research Unit, The Rayne Institute, St. Thomas' Hospital, London, UK and is the Managing Editor of the Lupus Journal. Oier Ateka-Barrutia, MD is based at the Hospital de Navarra, Pamplona, Spain. He has also worked alongside Dr Khamashta and Dr Bertolaccini as an overseas clinical fellow at the Lupus Research Unit, The Rayne Institute, St. Thomas$1 (BHospital, London, UK.s
History -- Epidemiology -- Antiphospholipid Antibodies -- Classification Criteria for APS -- Mortality, Morbidity, and Damage Associated with aPL -- Differences Between Primary and Secondary APS -- Clinical Features -- aPL and Transplantation -- Differential Diagnosis -- Management of APS.
Keywords: Medicine; Immunology; Dermatology; Internal medicine; Cardiology; Neurology; Rheumatology; Medicine & Public Health; Internal Medicine; Rheumatology; Cardiology; Neurology; Immunology; Dermatology